The first infrared beamline at the Middle East SESAME synchrotron facility. (13th September 2021) - Kamel, Gihan; Lefrancois, Stephane; Moreno, Thierry; Al-Najdawi, Mohammad; Momani, Yazeed; Abbadi, Anas; Paolucci, Giorgio; Dumas, Paul
Abstract : The design, construction, performance and operation of the first infrared beamline at the Middle East synchrotron light source facility SESAME is described. Abstract : SESAME (Synchrotron‐light for Experimental Science and Applications in the Middle East) is the only synchrotron light facility in the Middle East and neighboring regions, officially opened in 2017. Among the identification and construction of the first operational beamlines, infrared spectromicroscopy was selected as one of the two beamlines to be opened to the general users' program (the so‐called Day‐1 beamlines). Being one of the most demanded techniques by various scientific communities in the Middle East, the beamline has been designed and implemented in the framework of a collaboration agreement with the French synchrotron facility, SOLEIL. The design, construction and initial performances of the IR beamline (D02‐IR), nowadays operational, are reported.